Aromanians (Confluenţe Bibliologice, 2024)
The article describes the work AROMANIANS, written by Anastase N. Hânciu. The work addresses the issue of the Aromanians in various ﬁelds: trade, industry, arts, expansion, and civilization.The Aromanians (referred to in Romania as Macedonian Romanians, Macedo-Romanians, Macedono-Vlachs, or more commonly, Machidons) are a branch of Eastern Latinity, alongside the Daco-Romanians, Megleno-Romanians, and Istro-Romanians. The article provides information on the cultural heritage of the Aromanians, their occupations, and their characterization from linguistic, cultural, and political perspectives.
Keywords: Romanian history